Recent progress in metal-organic frameworks as active materials for supercapacitors. Issue 1 (January 2020) - Wang, Kuai-Bing; Xun, Qun; Zhang, Qichun
Highlights: An overview of MOFs and MOF composites as active materials for supercapacitors is provided. Recent progress in various MOFs branches for supercapacitors is reviewed. The limiting factors for practical applications of MOFs are commented. The superiority and the deficiency of various MOFs are systematically reviewed. Abstract: Metal-organic frameworks (MOFs), also quoted as porous coordination polymers (PCPs), are causing great concern in supercapacitors (SCs) field owing to their ultra-high surface-areas, tailorable pore-sizes and shapes, and diverse structural architectures. This review mainly focuses on the recent progress in various branches of MOFs materials including porous coordination networks, two-dimensional (2D) MOFs, entangled MOFs, polyoxometalate MOFs (POMOFs), heterometallic MOFs, and some new emerging MOFs, as well as their applications in SCs. The superiority and the deficiency of various MOF types were systematically introduced and summarized. Additionally, the challenges and perspectives relate to pristine MOFs and MOFs-based composites for the applications in SCs have also been discussed. We hope that our review could provide guiding frameworks to design and fabricate MOFs materials with more practical energy-storage applications. Graphic abstract: Recent progress on various branches of MOFs materials for SCs, including PCNs, 2D MOFs, entangled MOFs, POMOFs, heterometallic MOFs and new emerging MOFs, are reviewed. Image, graphical abstract